2015
DOI: 10.2134/jeq2015.03.0139
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Indicator and Pathogenic Bacteria and Their Antibiotic Resistance in Alluvial Groundwater of an Irrigated Agricultural Region with Dairies

Abstract: Surveys of microbiological groundwater quality were conducted in a region with intensive animal agriculture in California, USA. The survey included monitoring and domestic wells in eight concentrated animal feeding operations (CAFOs) and 200 small (domestic and community supply district) supply wells across the region. Campylobacter was not detected in groundwater, whereas Escherichia coli O157:H7 and Salmonella were each detected in 2 of 190 CAFO monitoring well samples. Nonpathogenic generic E. coli and Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…Depth to the water table for the monitoring wells was 3.4 m bgs, and the wells were sampled at a depth of 4.3 m bgs. A previous hydrologic analysis indicated that MW5 is primarily recharged from the manured corn field, MW6 receives partial recharge from the manured corn field and partial recharge from an adjacent unmanured orchard, and DOM is primarily recharged from the adjacent orchard with slight impact from the manured field [1012]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depth to the water table for the monitoring wells was 3.4 m bgs, and the wells were sampled at a depth of 4.3 m bgs. A previous hydrologic analysis indicated that MW5 is primarily recharged from the manured corn field, MW6 receives partial recharge from the manured corn field and partial recharge from an adjacent unmanured orchard, and DOM is primarily recharged from the adjacent orchard with slight impact from the manured field [1012]. …”
Section: Resultsmentioning
confidence: 99%
“…Particulates in the collected water were concentrated by tangential flow filtration [12, 55] using a peristaltic pump recirculating the water through a dialysis filter cartridge (Optiflux, Fresenius Inc). The collected water was concentrated to 300 mL and the filtrate was stored on ice until DNA extraction 12 hours later.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic residuals and organisms harboring antibiotic-resistant genes can be excreted into the environment through animal wastes [16,17,21]. Runoff can carry these elements into water sources [22]. Humans become exposed to antibiotic-resistant organisms by drinking and/or swimming in contaminated water, or by ingesting produce that was irrigated with contaminated water.…”
Section: Animal Environmentsmentioning
confidence: 99%
“…Recently, Li et al (2015) investigated microbiological contamination of domestic and community supply wells in California’s Central Valley, a region with intensive animal agriculture [22]. Approximately 5.9% and 10.3% of wells were positive for generic E. coli and Enterococcus spp., respectively, with significant associations observed between concentrations of enterococci and proximity of wells to animal feeding operations [22]. In Maryland, there are 12,200 registered farms, including a number of animal feeding operations [23].…”
Section: Introductionmentioning
confidence: 99%